Kompetensi Komunikasi Customer Service Sebagai Pendukung Kepuasan Nasabah - Yanti Herawati; Siti Komsiah (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
This research is motivated by the interest of researchers to examine the influence ofcustomer service communication competence on customer satisfaction with the researchobject of Bank Central Asia KCP Pondok Ungu. The purpose of this study was to determinethe magnitude of the influence of customer service communication competence on customersatisfaction. This research uses The Excellent of PR theory. The research method used isquantitative with an explanatory approach. The population in this study were 101customers of BCA KCP Pondok Ungu. The sampling technique used is non-probability withthe accidental sampling method. The results showed that the influence of customer servicecommunication competence on customer satisfaction was 67.2%, then 32.8% wasinfluenced by other things that were not included in this study.